The Surgical Treatment of Pelvic Bone Metastases - Daniel A. Müller; Rodolfo Capanna (Advances in Orthopedics)
Pelvic bone metastases are a growing concern in the field of orthopedic surgery. Patients with pelvic metastasis are individually different with different needs of treatment in order to attain the best possible quality of life despite the advanced stage of disease. A holistic collaboration among the oncologist, radiation therapist, and orthopedic surgeon is mandatory. Special attention has to be directed to osteolytic lesions in the periacetabular region as they can provoke pathological fractures and subsequent functional impairment. Different reconstruction techniques for the pelvis are available; the choice depends on the patient’s prognosis, size of the bone defect, and response of the tumor to adjuvant treatment. If all the conservative treatments are exhausted and the patient is not eligible for surgery, one of the various percutaneous ablation procedures can be considered. We propose a pelvic analogue to the treatment algorithm in long bone metastasis and a scoring system in pelvic metastasis. This algorithm aims to simplify the teamwork and to avoid under- or overtreatment of pelvic bone metastases.